Effects of Ampicillin-Amikacin and Ampicillin-Rifampin on Enterococci - Iannini, Paul B. (1976)
Fifty-seven clinical isolates of enterococcus were tested for susceptibility to 10 antibiotics in a microtiter broth dilution system. Amoxicillin, ampicillin, vancomycin, and rifampin inhibited all strains at concentrations easily achievable in blood. Resistance to rifampin developed rapidly. Of the aminoglycosides, gentamicin was most active, followed in decreasing order by tobramycin, amikacin, kanamycin, and streptomycin. High-level resistance to streptomycin was present in 26% of the strains and to kanamycin in 23% of the strains. Growth curve studies of selected strains revealed synergy with ampicillin-amikacin and antagonism with ampicillin-rifampin. It is suggested that ampicillin-gentamicin constitutes adequate initial therapy for enterococcal infections until the results of tests for high-level resistance to kanamycin and streptomycin are known and that clinical trails of ampicillin-amikacin are warranted.